Program Analysis of The Indonesian Industrial Chamber Of Commerce (Kadin) and Rokan Hulu Regency Regent in Increasing Entrepreneurial Interest - Alfa Syahputra (Publikasi Indonesia, 2024)
This study aims to analyse the program of the Indonesian Chamber of Commerce and Industry (KADIN) and Regent Rokan Hulu Regency in increasing entrepreneurial interest. This research uses qualitative methods by conducting case studies on the KADIN program in Rokan Hulu Regency. Data was collected through interviews and documentation and then analysed using descriptive techniques. The results showed that the KADIN and regent Rokan Hulu Regency programs have a role in increasing entrepreneurial interest in the Rokan Hulu community, primarily through programs held, coaching, and marketing. However, several obstacles to implementing this program remain, such as lack of support from local governments and public understanding that KADIN must provide business capital. Therefore, more effective efforts are needed to realise the KADIN program in Rokan Hulu Regency and increase interest in entrepreneurship in the community.